Efeito dos ácidos hexenurônicos e da lignina no desempenho da ozonólize, em diferentes pHs da reação - Ventorim Gustavo; Colodette Jorge Luiz (Química Nova, 2006)
The effect of pH on the performance of the ozonolysis stage in pulp production was evaluated for conventional and acid treated brown and oxygen delignified eucalyptus kraft pulps. The objective was to determine separately the effects of lignin and hexenuronic acid on the performance of the ozonolysis stage. The reaction of ozone with hexenuronic acid is less sensitive to pH than the reaction of ozone with lignin. The efficiency and the selectivity of the reaction of ozone with pulp decreases after removal of hexenuronic acids. Increasing up to 7.0 the pH during the ozonolysis is viable in the sequence Z/D(EOP)D, resulting in savings of H2SO4 (8,5 kg/tsa) and NaOH (5 kg/tsa), but is not recommended in the sequence Z/ED(PO).